Demographic potential of the Belarusian village: state and development prospects - Lin, Svetlana D.; Tihonova, Ludmila E. (Journal of the Belarusian State University. Economics, 2022)
The article is devoted to the analysis of modern trends and features of the development of demographic potential in rural Belarus on the basis of generalisation of statistical data. The peculiarities of the socio-demographic processes of rural settlements are studied. The main problems of the formation of the rural demographic potential are identified, a system of measures to solve them is proposed.